Comparison of the neuromuscular effects of two infusion rates of rocuronium in anesthetized pigs - Kamilla Pedersen; Linda Loisa Kruhøffer; Jens Lykkesfeldt; Birgitte Saima Kousholt (Acta Veterinaria Scandinavica, 2022)
Abstract Background: Neuromuscular blocking agents are frequently administered to pigs used for research. In humans, administration of the drugs is not without risk and may result in accidental awareness under general anaesthesia and postoperative residual neuromuscular blockade that can lead to serious respiratory complications. Despite the extensive administration, the pharmacodynamics of neuromuscular blocking agents are not thoroughly studied in pigs. Therefore, this study investigates the neuromuscular response of two infusion rates of rocuronium, a commonly used non-depolarizing neuromuscular blocking agent. A group of 14 female Danish Landrace-Yorkshire-Duroc pigs used for supervised surgical training, weighing 40.3 ± 2.1 kg (mean ± SD), were included in the study. They received a loading dose of 0.85 mg/kg rocuronium intravenously followed by infusion of either 2.5 mg/kg/hour (L, low dose) or 5 mg/kg/hour (H, high dose) rocuronium for 30 min. Neuromuscular monitoring was performed with acceleromyography using train-of-four (TOF) stimulation. Onset time, time to reappearance of T1, T4, TOF ratio 90% and 100% were recorded. Results: All pigs in group H experienced loss of T1 throughout rocuronium infusion, whereas six out of seven pigs in group L had reappearance of T1 during rocuronium infusion, with additional reappearance of T4 in three of these pigs. The time to recovery of TOF ratio 90% was 14.0 ± 5.4 (L) and 21.7 ± 6.1 (H) minutes and recovery to TOF ratio 100% was 18.7 ± 6.5 (L) and 27.9 ± 9.2 min (H) (mean ± SD). Substantial inter-animal variation in neuromuscular recovery time was observed. Conclusion The large inter-animal variation in pharmacodynamic profiles emphasizes that individual neuromuscular monitoring and titration to effect should be used routinely in research protocols that include rocuronium. In addition to other important measures, these actions are key in order to avoid overdosing and limit the risk of residual neuromuscular blockade.